The Correlation Between Students’ Self-Efficacy and English-Speaking Performance in Future Dream Monologues - Dwi Putri Sihotang Sihotang; Yenita Br Sembiring; Ira Maria Fran Lumbanbatu (Teaching English and Language Learning English Journal, 2025)
This study aimed to investigate the relationship between students’ self-efficacy and their English-speaking performance in delivering a monologue about future aspirations among 16 ninth-grade students at SMP PGRI 1 Medan. Self-efficacy, defined as students’ belief in their ability to accomplish a task, is considered an important factor influencing language learning, particularly speaking skills, which require confidence, fluency, and organization. Despite receiving English instruction, students often encounter difficulties in expressing their ideas due to limited vocabulary, anxiety, and the influence of their native accents. This study employed a quantitative correlational approach. Data on self-efficacy were collected through a structured questionnaire, while students’ speaking performance was evaluated using recorded monologues. The relationship between the variables was analyzed using Pearson’s Product-Moment Correlation to determine the extent to which self-efficacy influences students’ speaking performance. The results revealed a positive correlation between self-efficacy and speaking performance; however, the correlation was not statistically significant. This indicates that students with higher self-efficacy tended to demonstrate better speaking outcomes, although the relationship was not strong enough to draw definitive conclusions. The findings emphasize the importance of fostering self-efficacy through guided practice, feedback, and motivational activities to enhance students’ speaking abilities. Moreover, this study provides insights into how psychological factors can influence language performance in monologue tasks.